SIMULASI NUMERIK HAMBATAN DAN POLA ALIRAN BARGE MENGGUNAKAN METODE CFD - Prameswari, Grandys; Puspita, Hery Indria Dwi; Sakinah, Wazirotus; ., Rudianto; Arianto, Pratama Yuli (Jurusan Teknik Mesin, 2024)
Barge is a ship that does not have a propulsion and must be towed by a tugboat to sail Therefore, the barge is pulled by a tugboat to sail. This causes the stern area of the barge to be installed with a skeg to support the ship's performance while sailing. One of the performance parameters is the resistance and flow pattern of the barge. Previous research recommended a straight longitudinal skeg at the stern of the barge. This paper continues the recommendation by applying a numerical simulation using the Computational Fluid Dynamics (CFD) method to predict the resistance and flow pattern of the barge due to the skeg used. The CFD method was chosen because of being able to provide accurate, fast, and optimal results. By knowing the resistance and flow pattern values, the results of this study can be used to calculate the amount of bollard pull required by the barge to be towed by the tugboat. The results obtained in this study are the highest resistance at 7 knots of 269.952 kN and the lowest resistance occurs at 4 knots of 89.206 kN. The flow pattern formed in the barge area can be concluded that turbulence mostly occurs in the stern area of the ship due to the interaction of wake, water flow and skeg position. Keywords: Barge, Skeg, Resistance, Flow Pattern